Evaluation of dairy potential of Bunaji and Sokoto Gudali breeds - Johnson, A.O.; Buvanendran, V.; Dim, N.I. (NAPRI, 1986)
The study was carried out to investigate the milk yield potential of Bunaji and Sokoto Gudali breeds, the environmental factors influencing dairy traits and to estimate the genetic parameters of some of the economic dairy traits. The data were 2177 records from 545 Bunaji cows and 928 records from 216 Sokoto Gudali cows covering 1934 to 1957. The animals were fed concentrates and milked twice per day. Least square procedure was used to analyze the data. The variance analyzed showed significant effects (p0.05). 305-day milk yield, lactation length, milk yield per day of calving interval and birth weight were moderate to high in heritability for both breeds, but calving interval, dry period and age at first calving were low in heritability estimates for milk yield.